Determining Factors in Developing Quality Management (QM) Model in Public and Private Organizations in the Philippines: A Literature Review (American Journal of Multidisciplinary Research and Innovation, 2023)
In this paper 79 randomly selected research papers published in the refereed journals in quality management practices and models have been reviewed. The papers are classified based on the year in which they were published, based on specific countries, and finally public or private industry type. Based on the analysis of reviewed papers, 23 determining factors in developing a quality management model have been identified. Leadership and management were found to be highly talked about as the determining factors in developing the quality management model, therefore the papers further analyzed the importance of quality practices in the organization. This paper has also provided the discussion, conclusions, and future research directions.